PROBLEMATIC INTERNET USE PADA REMAJA: ANALISIS BIBLIOMETRIK - Andrianie, Prilya Shanty; Purwandari, Eny; Taufik, Taufik (Jurnal Psikologi, 2024)
Apart from providing various conveniences, excessive internet use can also have negative impacts, one of which is problematic internet use (PIU). This research aims to find out studies regarding problematic internet use in teenagers so that further research can be carried out. The research method used is a biometric analysis using VOSviewer on published articles indexed by Scopus from 2018 to 2023. The research results show that searching journals on the scopus.com site with the keyword "Problematic Internet Use" brings up 413 journals. After that, it was reduced based on four aspects, namely (1) scientific articles written in English, (2) literature in the form of scientific articles published in Scopus-indexed journals, (3) articles published in 2018-2023, and (4) open journals. access. After carrying out the exclusion process based on these limitations, 101 journals were included. Based on data on the development of Scopus-indexed journals regarding problematic internet use from 2018 to 2023, the highest development was in 2022 with 25 journals and the lowest was in 2019 with 10 journals. In author collaboration, there were 406 authors but only 17 authors collaborated and were members of five groups. This shows the lack of significance of collaboration between authors. Apart from that, several research variables have opportunities for further research, such as those related to PIU prevention, family relationships, and emotional regulation.